EVALUASI PROSES ATAS KETERLAMBATAN PENGIRIMAN PAKET DI PERUSAHAAN JASA & LOGISTIK KANTOR CABANG PT XYZ - Aisah Dinda Nurhalizah Mawardy; Indro Kirono (MANAJEMEN DEWANTARA, 2026)
This study aims to evaluate the distribution process and identify the main factors causing package delivery delays at the branch office of PT XYZ, as well as to propose improvement strategies to enhance on-time delivery performance. This research employs a descriptive qualitative approach using observations, interviews, and documentation as data collection techniques. Data analysis is conducted using the Fishbone Diagram (6M) to identify the root causes of delays and the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) framework as a systematic process improvement method. The results indicate that delivery delays are mainly caused by three dominant factors: human resources, particularly in handling heavy packages; work methods, especially delays in real-time data entry at service counters; and technology, due to unstable tracking systems and delayed data updates. The proposed improvement strategies include implementing real-time data entry, adding dedicated staff for peak hours, optimizing digital tracking systems, and regulating courier workload distribution. These improvements are expected to enhance distribution efficiency and improve on-time delivery performance at the branch office of PT XYZ